Elimination of plasmid pMG110 from Escherichia coli by novobiocin and other inhibitors of DNA gyrase. - Hooper, D C (1984)
The ability of novobiocin to eliminate (cure) the wild-type plasmid pMG110 from Escherichia coli has been compared with that of other inhibitors of the gyrase B subunit and of the gyrase A subunit. Novobiocin eliminated pMG110 , producing over 99% plasmid loss at concentrations two- to eightfold below the MIC for bacterial growth. Structurally related compounds ( clorobiocin , coumermycin A1, isobutyryl novenamine , and decarbamyl novobiocin) varied in their ability to eliminate pMG110 . Higher concentrations of drugs were required to eliminate pMG110 from a gyrB( Cour ) strain, implicating DNA gyrase in the curing phenomenon. For these drugs, the ratio of the concentration effecting maximal plasmid elimination to the MIC varied from 0.16 to 1.1, indicating that curing cannot be explained simply by inhibition of a pool of DNA gyrase equally available for replication of the bacterial chromosome and the plasmid DNA molecule. Inhibitors of the gyrase A subunit, nalidixic acid and oxolinic acid, eliminated pMG110 only to variable low levels. The differences in the ability of the gyrase A and B subunit antagonists to eliminate plasmids are discussed.